2003
DOI: 10.1046/j.1525-1314.2003.00476.x
|View full text |Cite
|
Sign up to set email alerts
|

New constraints on metamorphism in the Rauer Group, Prydz Bay, east Antarctica

Abstract: Granulite facies metapelites of the Mather and Filla Paragneisses within the Rauer Group, east Antarctica, possess markedly different compositions. The metamorphic evolution of the two metapelite types has been interpreted as temporally distinct, with the Rauer Group preserving at least two distinct granulite facies tectonothermal episodes. Calculated P–T pseudosections and orthopyroxene Al content indicate the revised maximum‐preserved P–T conditions within the Mather Paragneiss to lie in the vicinity of 950–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 76 publications
(232 reference statements)
7
88
0
2
Order By: Relevance
“…Based on their interpretation that 980-580 Ma zircons in their Mather Paragneiss sample were detrital grains of varied metamorphic provenance, Kelsey et al (2008) concluded that the Mather Paragneiss was not older than 580 Ma, citing this as proof that the UHT metamorphism occurred in the Prydz Tectonic Event from 575 through to 510 Ma, in accord with evidence from monazite chemical dating (Kelsey et al 2003b(Kelsey et al , 2007. As argued above, the broad range in Neoproterozoic ages could plausibly be the result of variable resetting of early Neoproterozoic detrital grains by the Prydz Tectonic Event, so that the Mather Paragneiss could have been deposited as early as 1000 Ma but after the Rauer Tectonic Event.…”
Section: Relationships Between Archaean and Proterozoic Crustal Domaimentioning
confidence: 93%
See 2 more Smart Citations
“…Based on their interpretation that 980-580 Ma zircons in their Mather Paragneiss sample were detrital grains of varied metamorphic provenance, Kelsey et al (2008) concluded that the Mather Paragneiss was not older than 580 Ma, citing this as proof that the UHT metamorphism occurred in the Prydz Tectonic Event from 575 through to 510 Ma, in accord with evidence from monazite chemical dating (Kelsey et al 2003b(Kelsey et al , 2007. As argued above, the broad range in Neoproterozoic ages could plausibly be the result of variable resetting of early Neoproterozoic detrital grains by the Prydz Tectonic Event, so that the Mather Paragneiss could have been deposited as early as 1000 Ma but after the Rauer Tectonic Event.…”
Section: Relationships Between Archaean and Proterozoic Crustal Domaimentioning
confidence: 93%
“…Kelsey et al (2003b) reported monazite electron microprobe chemical ages for the Mather Paragneiss that ranged from 521 ± 8 to 500 ± 6 Ma. These data were complemented by in-situ results from two further samples that yielded ages of up to 544 ± 11 Ma for monazites hosted in or exhumed from garnet porphyroblasts (Kelsey et al, 2007).…”
Section: Relationships Between Archaean and Proterozoic Crustal Domaimentioning
confidence: 99%
See 1 more Smart Citation
“…Ouzegane et al, 2003) assemblages. As a result there is considerable uncertainty in the dP/dT slopes of such ITD paths, which may involve considerable cooling contemporaneous with decompression, a point well emphasised recently by Kelsey et al (2003a;2003b).…”
Section: Pelites: Uht Mineral Assemblages In the Fmas And Near Fmas Smentioning
confidence: 99%
“…2a) but have the advantages of being adjustable in the light of further experiments in adjacent or related systems and usable as frameworks for quantitative pseudosections that are based on the same thermodynamic data. Ouzegane et al (2003) and Kelsey et al (2003a;2003b) have adopted this approach to produce calculated grids in KFMASH and pseudosections in KF-MASH / NCKFMASH in order to interpret Grt + Spr + Crn and Opx + Sil + Qz UHT assemblages respectively. Figure 3a depicts a partial petrogenetic grid in KFMASH based on the experiments of Carrington and Harley (1995a) and contoured for the percentage of Mg Tschermaks component in orthopyroxene following Harley and Thompson (2004).…”
Section: Pelites: Kfmash Complex Systems and The Pseudosection Apprmentioning
confidence: 99%